Konstruksi Ilmu Menurut Nashiruddin Ath-Thusi - Mahdi, Mahdi; Yunus, Firdaus M. (Lembaga Penelitian dan Pengabdian kepada Masyarakat of Universitas Islam Negeri Jurai Siwo Lampung, 2023)
Nashiruddin Ath-Thusi (1202-1274 M /597- 672 H) is better known as an astronomer than a philosopher, this is because he built an observatory Rasad Khanah in Maragha Azerbaijan, his work in philosophy was the endeavor and pioneer of the revival movement (revivalis), for trying to revive Ibn Sina's philosophical concept which had sunk due to the